BRS ÂMBAR, A CANNING PEACH CULTIVAR WITH GOOD FLAVOR IN NATURA - RASEIRA, Maria do Carmo Bassols; NAKASU, Bonifácio; PEREIRA, José Francisco Martins (Scientia Agraria, 2010)
Consumers are still very much atracted by fruit size. Peach selection Conserva 803, which was released by Embrapa Clima Temperado, in 2009, as cultivar BRS Âmbar match this demand. BRS Âmbar has shown, over the years, a consistent production of excellent size fruits, with an average weight superior to 130 g. This cultivar is originated from a controlled cross between cv. Esmeralda and selection Conserva 555. Fruits of ‘BRS Âmbar´ have better taste, larger size and better shape than the ones from cv. Esmeralda, but are less firm. It is one more option of processing type peaches for end of November or beginning of December.